Effect of Temperature and Concentration on the Physical Properties of Cholesteryl Pelargonate Near Transition Temperatures - Gajghate, V.; Kanwar, A. (Journal of Scientific Research, 2021)
Thermodynamic and acoustical study of cholesteric liquid crystal (CLC) was carried out near phase transition temperatures using an ultrasonic interferometer. The study of ultrasonic waves and related thermo-acoustical parameters provides information in understanding the nature of molecular interactions associated with liquid crystals. A statistical mechanical approach is used to calculate the viscosity of samples. The characteristic textures and phase transition temperatures are obtained with Polarizing Microscopy (POM). Fabry Perot scattering studies (FPSS) are used to ascertain the phase transition temperatures of CLC. The thermo-acoustical parameters have been calculated using experimental data with well-known formulae. The acoustical parameters show variation with temperature as well as with concentration of CLC. Anomalous behavior of these parameters is noticed at the clearing temperature of CLC. The variation of the parameters is explained in terms of solute-solvent molecular interactions in the solution. The molecular behavior, structural changes, and intermolecular interactions between CLC and solvent are discussed in detail.